Black hole formation in the context of dissipative dark matter. Issue 3 (15th March 2019) - Latif, M A; Lupi, A; Schleicher, D R G; D'Amico, G; Panci, P; Bovino, S
Abstract: Black holes with masses of $\rm 10^6\text{-}10^9\, M_{\odot }$ dwell in the centres of most galaxies, but their formation mechanisms are not well known. A subdominant dissipative component of dark matter with similar properties to the ordinary baryons, known as mirror dark matter, may collapse to form massive black holes during the epoch of first galaxies formation. In this study, we explore the possibility of massive black hole formation via this alternative scenario. We perform three-dimensional cosmological simulations for four distinct haloes and compare their thermal, chemical, and dynamical evolution in both the ordinary and the mirror sectors. We find that the collapse of haloes is significantly delayed in the mirror sector due to the lack of $\rm H_2$ cooling and only haloes with masses above $\rm \ge\!10^7\, M_{\odot }$ are formed. Overall, the mass inflow rates are $\rm \ge\!10^{-2}\, M_{\odot }\, yr^{ -1}$ and there is less fragmentation. This suggests that the conditions for the formation of massive objects, including black holes, are more favourable in the mirror sector.